Characterization Methods of Amorphous Form Stability in Solid Dispersion : A Review - Maria Elvina Tresia Butarbutar; Nasrul Wathoni; Yoga Windu Wardhana (Universitas Padjadjaran (Unpad), 2020)
Solubility as a cause of ineffective active pharmaceutical ingredients (API) needs to be a concern. One of the solutions to increase the solubility by choosing active ingredients in the amorphous form. However, the amorphous form tends to be unstable because it has high Gibbs free energy and molecular mobility. To overcome those properties solid dispersion methods can be an answer. The dispersion of the amorphous form in the polymer is expected to prevent the transformation of API to crystal stable form. The solid dispersion (SD) resulted needs for physicochemical characterization to prove the ability of SD to maintain the amorphous form. Therefore, the physicochemical properties of the amorphous solid dispersions (ASDs) have to analyze there in any interactions that are able to occur between the drug and the polymer. Also for evaluate the stability of the ASDs within a certain period. In the article presents, some articles related with ASDs and its characterization will studying, include several product on the market as example. The number of literature used in this article is 69 articles.Keywords: Solubility, amorphous for, solid dispersion, characterization ASDs.